Update on the use of erythropoiesis-stimulating agents (ESAs) for the management of anemia of multiple myeloma and lymphoma - Katodritou, E.; Dimopoulos, M.A.; Zervas, K.; Terpos, E. (Cancer Treatment Reviews, 2009)
Anemia is a common side-effect of patients with multiple myeloma (MM) and lymphoma. The etiology is complex, but the main cause is the underlying mechanism of anemia of chronic disease, which is characterized among others, by impairment of iron metabolism and consequently iron restricted erythropoiesis (IRE), resulting from the up-regulation of the iron distributing regulator, hepcidin. Erythopoiesis-stimulating agents (ESAs) have been the standard of care since early 90's offering high response rates and improving the quality of life of the patients. However, the role of ESAs in the treatment of cancer-related anemia has been questioned recently, due to the growing evidence which support that ESAs may be associated with increased risk for thrombosis and may have a detrimental impact on patients' survival. Under the light of the recent considerations, the place of ESAs in the management of cancer-related anemia has been reassigned. Regarding the management of anemia in MM or lymphoma, the updated American Society of Clinical Oncology/American Society of Hematology (ASCO/ASH) 2007 clinical practice guidelines on the use of ESAs in cancer-related anemia, recommended that ESAs should be preferably omitted in patients planned to receive chemotherapy and applied in case that anemia does not improve over treatment. The quest for reliable predictors for response to ESAs and for indicators of IRE which plays a major etiological role for the development of anemia of cancer still remains an open issue. In the current review we present an update on ESAs use in anemia of MM and lymphoma. © 2009 Elsevier Ltd. All rights reserved.
Keywords: Anemia; Complications; Erythropoiesis-stimulating agents; Lymphoma; multiple myeloma; Quality of Life; Survival; Thrombosis